2023
DOI: 10.3390/ijms24065918
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles of COVID-19 Patients Reflect Inflammation, Thrombogenicity, and Disease Severity

Abstract: Severe COVID-19 infections present with cytokine storms, hypercoagulation, and acute respiratory distress syndrome, with extracellular vesicles (EVs) being involved in coagulation and inflammation. This study aimed to determine whether coagulation profiles and EVs reflect COVID-19 disease severity. Thirty-six patients with symptomatic COVID-19 infection with mild/moderate/severe disease (12 in each group) were analyzed. Sixteen healthy individuals served as controls. Coagulation profiles and EV characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Prior investigations revealed that EPCR interacting with coagulation proteases (namely, thrombin or tissue factor), or anticoagulant proteins (namely, activated protein C) to specific cell receptors on mononuclear or endothelial cells may influence cytokine synthesis (e.g., TNF-a, IL-1, IL-6, and IL-8, etc.) or inflammatory cell apoptosis ( 27 , 29 31 ). Furthermore, EPCR itself possesses anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations revealed that EPCR interacting with coagulation proteases (namely, thrombin or tissue factor), or anticoagulant proteins (namely, activated protein C) to specific cell receptors on mononuclear or endothelial cells may influence cytokine synthesis (e.g., TNF-a, IL-1, IL-6, and IL-8, etc.) or inflammatory cell apoptosis ( 27 , 29 31 ). Furthermore, EPCR itself possesses anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis identified target genes that encode proteins located in exosomes that were crucial to vesicle transport, such as CD63 , ATP6V1D , and CHMP1A . CD63, commonly used as an exosome marker, increased protein expression, and correlated to higher exosome levels in severely ill COVID-19 patients ( Aharon et al, 2023 ). In addition, CD63 expression was increased in plasma cell-free RNA sequences of severe COVID-19 patients ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…124 The percentage of expression of CD4 and CD8 are higher in mild and severe COVID-19 infections, respectively, than in healthy people. 125 CD8 T cells can persist for up to 6 months after COVID-19 infection with continuous cytotoxic effect. The expression of CD14 was found to be higher in severe COVID-19 cases than in mild and nondiseased people.…”
Section: Neurological Disorders In Covid-19 and The Role Of Exosomes ...mentioning
confidence: 99%
“…In addition to the previous immune response after COVID-19 infection, cell-mediated immunity is highly stimulated after its recognition of viral antigens, resulting in the increase of secreted ECVs from T-cells and the promotion of inflammation. 125 Furthermore, the depletion of B cells after the administration of anti-CD20 monoclonal antibody could facilitate the long-COVID effect. 126 In severe COVID-19 infection, the exosome cargo was found to contain C1R, which has a role in activation of complement 1 complex, inflammation, and endothelial dysfunction.…”
Section: Neurological Disorders In Covid-19 and The Role Of Exosomes ...mentioning
confidence: 99%